Sintomas depressivos e ansiosos em mães de recém-nascidos com e sem malformações - Perosa, Gimol Benzaquen [UNESP]; Canavez, Isabela Cristina; Silveira, Flávia Cristina Pereira [UNESP]; Padovani, Flávia Helena Pereira [UNESP]; Peraçoli, José Carlos [UNESP] (My University, 2009)
Purpose: the main goal of this study is to evaluate the emotional conditions among mothers of newborns with visible malformation (Group M) and mothers of eutrophic newborns (Group E) soon after birth. Methods: twenty-two mothers from the Group M were matched by age and number of children to 22 mothers of the Group E. They were assessed through the Beck Depression Inventory (BDI) and the State-Trait Anxiety Inventory (STAI). The data were complemented by interviews and analyses of the medical files of both mother and child. Results: the results have shown significant differences in the mean scores of the three subscales (trait anxiety, state anxiety, dysphoria/depression) between the two groups of mothers. In terms of clinical signs, there were a significantly larger percentage of mothers from Group M identified with depression and anxiety after the child's birth, and for both conditions when compared with mothers from Group E. Although the results may reflect characteristics of the maternal personality, the trait anxiety was significantly more evident in mothers of malformed children, especially due to the child's health condition, its referral to the ICU and his/her condition regarding their future life. Conclusion: the percentage of mothers with clinical depression and anxiety suggests the need for either individual or group support to attend the needs of the mothers and mitigate the adverse effects of stressors throughout the child's development. Support should also be provided during pregnancy, when the mothers currently receive the news about the malformation.
Depressive and anxious symptoms in mothers of newborns with and without malformations
Keywords: Congenital abnormalities; Depression; Maternal anxiety; Mental health